Aplikasi Android Untuk Reservasi Lapangan Futsal Menggunakan Metode First In First Out (FIFO) - Jonathan Zebina Laala; Chairunnisa Ar. Lamasitudju; Ryfial Azhar; Rahmah Laila; Wirdayanti; Miftah (The Indonesian Journal of Computer Science, 2024)
Technology facilitates the process of futsal field rental, such as payment queueing and real-time monitoring. An Android application has been developed to manage payment queueing and futsal field rental at Novega Futsal Court, addressing inefficiencies of traditional methods that decrease customer satisfaction. Utilizing Rapid Application Development (RAD) and First In First Out (FIFO) method, this application designed expedite and enhance the queueing process. Data was collected through direct interaction with respondents and on-site observation, while its development involved the use of React Native and Node.js. Testing results indicate the application functions as expected, enabling users to easily rent and pay, and assisting managers in efficiently organizing queues. This application enhances service efficiency and customer satisfaction, making a positive contribution to technology-based futsal management.